2016
DOI: 10.17511/ijpr.2016.i05.14
|View full text |Cite
|
Sign up to set email alerts
|

Age stratified Seroprevalence of Cytomegalo virus in children

Abstract: Introduction: Cytomegalovirus seroprevalance in developing countries is found to be high but there is no recent study done in India especially in children. Primary CMV infection is asymptomatic, but the virus remains latent in organs and children shed the virus in their urine and saliva for a long period. Primary infection can cause major consequences in growing fetus, premature infants, and immune deficient individuals especially those with AIDS. It highlights the need for sero negative blood for transfusion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The prevalence of CMV infection in age groups 1-28 days and 28 days to 1 year were 92.8% and 87.5% respectively, suggesting that CMV infection is highly prevalent in Indian children. However, passive transfer of CMV IgG antibodies from the mother could be a confounding factor [ 22 ]. Dollard et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of CMV infection in age groups 1-28 days and 28 days to 1 year were 92.8% and 87.5% respectively, suggesting that CMV infection is highly prevalent in Indian children. However, passive transfer of CMV IgG antibodies from the mother could be a confounding factor [ 22 ]. Dollard et al .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of CMV infection in age groups 1-28 days and 28 days to 1 year were 92.8% and 87.5% respectively, suggesting that CMV infection is highly prevalent in Indian children. However, passive transfer of CMV IgG antibodies from the mother could be a confounding factor [22]. Dollard et al found presence of CMV IgG in 27% of healthy children from 6 months to 5 years, of which 3 out of 13 positives were also CMV IgM positive, suggestive of recent primary infection.…”
Section: Discussionmentioning
confidence: 99%